Mathematical tools in a digital world - Durity, Anthony (2012)
There are many vantage points from which to gain a perspective on digital culture. The intersection of mathematics and mathematical tools with all things digital is one such vantage point. This implies an inspection of mathematical software. The broad lines that can be taken are the practice, education and application of mathematics. This thesis focuses on practice and application, disregarding education.